Revealing Humor in the Selected Episodes of Comedy Series Mind Your Language Script Using Gricean Conversational Maxims - M Masqotul Imam Romadlani (Fakultas Ilmu Budaya, 2018)
This research is conducted to examine how the non-observance maxims are applied to create humor in the selected episodes of Mind Your Language situation comedy script. This research also identifies how the characters in Mind Your Language are being non-observance to the maxim to create humor and what types of non-observance maxim mostly occur in that sitcom. Grice’s theory of cooperative principle has a crucial role in analyzing utterances as main tool for analysis. Theory of humor and context of situation are also applied to aid deeper understanding about the creation of humor and about how the speakers produce utterances which are breaking the rule of cooperative principle. This research applies the qualitative and quantitative research. The qualitative research which is used in this study is to describe and interpret during the process of analyzing the data. The qualitative research is used to analyze in detail the process of humor creation in that sitcom. The quantitative research is taking a part to calculate the sum of the non-observance maxims occurred and then grouping each maxim which are failed to observe. Purposive sampling technique is used to choose the data by determining utterances which is containing non-observance maxim and the emergence of canned laughter at the same time. The Mind Your Language sitcom script was accessed on http://subsmax.com/subtitlesmovie/mind-your-language-english on June 4th, 2016 at 11:43 pm. The finding shows that there are 73 utterances containing non-observance maxim and the emergence of canned laughter at the same time. One utterance is identified as flouted maxim, 18 utterances are identified as violated maxim, 48 utterances are identified as infringed maxim, an utterance is identified as opted out maxim, and 5 utterances are identified as double non-observance maxims, infringed and violated maxim at the same time. From the findings above, the most dominant non-observance maxim which occurs in Mind Your Language sitcom to create humor is infringing maxim with its 48 utterances. Infringing maxim is an unawareness or unintentional failure to observe to the maxim. Grice proposes that the term “infringing a maxim” for the failure in observing a maxim that is caused by imperfect linguistic performance, specifically in imperfect command of language and impaired performance. Imperfect command of language is usually done by a young child or a language learner, while impaired performance is caused by nervousness, drunkenness, excitement, and so on. The findings also show that the infringed maxim occurs because of some factors. The first is because of the characters’ limited knowledge about English. It leads the characters in misunderstanding condition caused by misheard or mispronunciation. The second factor is because of different understanding about some English words from each character. The third factor is because of the use of inappropriate English word in some contexts on the dialogue. The last, some humorous utterances are also created because of excitement of some amusing moment that influence other characters’ way in uttering something. It leads the character uttering unexpected response which creates humor.
Reupload file repositori 24 februari 2026_Kurnadi
Keywords: Gricean Conversational Maxims